An accurate wireless data transmission and low power consumption of foot plantar pressure measurements - Mohamad Ghazali, Aina Mardhiyah; Wan Hasan, Wan Zuha; Hamidun, Mohd. Nizar; Sabry, Ahmed H.; Ahmed, S. A.; Wada, Chikamune (Elsevier, 2015)

(untitled)
The need for an accurate real time measurements for the foot plantar pressure, especially in gait analysis, is important and always under research because its flow in human health. This work proposes an accurate, very low power consumption wireless data transmission for monitoring and analyses the diagnosis based on two XBee S1RF Modules, one functionas a base (receiver) which is connected to PC while the other collects the force/pressure sensors output and acts as a remote (data acquisition unit). The developed system consists of 4 resistive pressure sensors attached to an insole. Sensors are placed at four effective pressure points and interfaced with a wireless node and suitable conditioning circuit board. High speed rate and very low power consumption of data process made this technique useful for this application. Light weight lithium ion polymer, 16 gm, 2.96 W.h, 3.6 V can operate the data acquisition and RF remote circuit with about 22.4 hours. A graphical user interface using MATLAB is used to plot data curves for different measurements.